The Effects of Lead, Cadmium, Mercury and Arsenic on Fish - Al-Abyadh, Mokhtar (LAP Lambert Academic Publishing, 2018)
Increased humanely use of Toxic Heavy Metals such as Lead (Pb), Cadmium (Cd), Mercury (Hg) and Arsenic (As) and their access to the marine environment has caused much concern over the last century. These Toxic Heavy Metals known in the marine environment may lead to toxic effects, even if they are relatively low concentrations at present in living organisms. In this study, the samples were collected from the three different Cities of Yemeni coasts. The Cities are named as Al-Hodaeidah, Aden and AL-Mukalla, the trial was undertaken for the period of winter 2011, summer 2012 and winter 2013. Fresh samples were procured from the showrooms for sale at the public auction adjacent to the fishing grounds. Four species of fish were collected and (emperor) Lethrinus mahsena, (Longtail tuna) Thunnus tonggol, (Pickhandle Barracuda) Sphyraena jello and (Areolate grouper) Epinephelus areolatus. The samples were as 81 samples of Filtered Surface Seawater, Sediment and 324 fish samples (for Muscle, Lver and Gills) ), Which were digested using appropriate acids, tools and different methods, and then measured the concentrations of heavy metals.